PENGARUH DIVERSIFIKASI PORTOFOLIO PEMBIAYAAN TERHADAP KESEHATAN BANK SYARIAH DI INDONESIA TAHUN 2020-2022 - Mahendra, Taufik Riza (Studia Economica : Jurnal Ekonomi Islam, 2023)
The soundness of the bank is the result of qualitative assessment of various aspects affecting the status or performance of the bank through the assessment of capital, asset quality , management, profitability, liquidity and sensitivity to market risk. The increasing use of Islamic banks in the daily lives of Indonesians, in addition to bringing benefits, also has an impact on the health risks of Islamic banks themselves. The purpose of this study is to know the financial development of Islamic banks in Indonesia and to know the impact of financial diversification on the health of Islamic banks in Indonesia itself. The method used in this study is to use quantitative method for the purpose of descriptive research. The research results show that variable X1, i.e. contract-based financial portfolio diversification, has a significant impact on the health of Islamic banking in Indonesia in the period 2020-2023. where these results are known to have a significance value of 0.000 or 0%. This value is lower than the 0.05 or 5% significance value.